One‐year results of the ICON (ionic versus non‐ionic contrast to obviate worsening nephropathy after angioplasty in chronic renal failure patients) Study. Issue 4 (20th October 2015) - Giustino, Gennaro; Baber, Usman; Mastoris, Ioannis; Vlachojannis, Georgios J.; Yu, Jennifer; Teirstein, Paul S.; Downey, William E.; Batchelor, Wayne B.; Casterella, Peter J.; Nikolsky, Eugenia; Wong, S. Chiu; Theodoropoulos, Kleanthis N.; et al.
Abstract : Background: Long‐term clinical outcomes after exposure to non‐ionic iso‐osmolar contrast medium (IOCM) or ionic low‐osmolar CM (LOCM) in patients with chronic kidney disease (CKD) undergoing coronary angiography are unclear. Methods: The ICON trial was a prospective, double‐blinded, multicentre study that randomly assigned 146 patients with CKD undergoing coronary angiography with or without percutaneous coronary intervention to the non‐ionic IOCM Iodixanol or the ionic LOCM Ioxaglate. We report the 1‐year clinical outcomes. Results: After randomization, baseline and procedural characteristics were well‐matched between the two groups. At 1 year, three deaths (4.1%) occurred in the ioxaglate and nine deaths in the iodixanol group (13.6%, P  = 0.07). The cardiac death rate at 1 year was 2.7% in the ioxaglate group and 9.1% in the iodixanol group ( P  = 0.07). There were no significant differences in the rates of myocardial infarction (1.4% vs. 1.5%; P  = 1.00) and repeated revascularization (6.8% vs. 9.1%; P  = 0.75). Conclusions: The use of ionic LOCM ioxaglate was associated with a numerically lower mortality at 1 year as compared to iodixanol in patients who underwent cardiac catheterization. Future studies evaluating long‐term safety following exposure to different types of CM are warranted. © 2015 Wiley Periodicals, Inc.